2006
DOI: 10.4065/81.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Electrophysiologic Monitors With Clinical Assessment of Level of Sedation

Abstract: On the basis of our results, these EEG-based monitors cannot reliably distinguish between light and deep sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 40 publications
2
45
1
2
Order By: Relevance
“…Our study found a moderate correlation between sedation and dexmedetomidine in elderly patients, in accordance with Christopher et al In their study, the older patients (aged above 55 years) had weaker correlations between Patient State Analyzer data and OAA/S scores compared with the younger patients 31. The correlation between electrophysiological and clinical assessments of sedation level remains controversial 31, 32, 33, 34…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study found a moderate correlation between sedation and dexmedetomidine in elderly patients, in accordance with Christopher et al In their study, the older patients (aged above 55 years) had weaker correlations between Patient State Analyzer data and OAA/S scores compared with the younger patients 31. The correlation between electrophysiological and clinical assessments of sedation level remains controversial 31, 32, 33, 34…”
Section: Discussionsupporting
confidence: 89%
“…The correlation between electrophysiological and clinical assessments of sedation level remains controversial 31, 32, 33, 34…”
Section: Discussionmentioning
confidence: 99%
“…Although administration of many drugs can be avoided or limited with regional anesthetic techniques and reductions in the prevalence of postoperative delirium have been observed with regional anesthesia, these results are inconsistent. 27,28 This inconsistency may be explained by reports that sedation levels consistent with general anesthesia are frequently observed during regional anesthesia [29][30][31][32] and, at least in an intensive care setting, that sedation level is an important risk factor for delirium. 23 The intravenous anesthetic propofol is commonly used to provide intraoperative sedation during spinal anesthesia and other regional anesthetics.…”
Section: Discussionmentioning
confidence: 95%
“…A score of 0 represents total cortical silence, and the number continues upwards in a nonlinear path to 100 with increasing cortical activity. Evaluations of the PSI and RSS in studies in intensive care units have shown good correlation between the two scales (14,15).…”
Section: Protocolmentioning
confidence: 99%